Materials Informatics for Dark Matter Detection. Issue 11 (10th September 2018) - Geilhufe, R. Matthias; Olsthoorn, Bart; Ferella, Alfredo D.; Koski, Timo; Kahlhoefer, Felix; Conrad, Jan; Balatsky, Alexander V.
Abstract : Dark Matter particles are commonly assumed to be weakly interacting massive particles (WIMPs) with a mass in the GeV to TeV range. However, recent interest has shifted toward lighter WIMPs, which are more difficult to probe experimentally. A detection of sub‐GeV WIMPs will require the use of small gap materials in sensors. Using recent estimates of the WIMP mass, we identify the relevant target space toward small gap materials (100 to 10 meV). Dirac Materials, a class of small‐ or zero‐gap materials, emerge as natural candidates for sensors for Dark Matter detection. We propose the use of informatics tools to rapidly assay materials band structures to search for small gap semiconductors and semimetals, rather than focusing on a few preselected compounds. As a specific example of the proposed strategy, we use the organic materials database (https://omdb.diracmaterials.org ) to identify organic candidates for sensors: the narrow band gap semiconductors BNQ‐TTF and DEBTTT with gaps of 40 and 38 meV, and the Dirac‐line semimetal (BEDT‐TTF)·Br which exhibits a tiny gap of ≈50 meV when spin‐orbit coupling is included. We outline a novel and powerful approach to search for dark matter detection sensor materials by means of a rapid assay of materials using informatics tools. Abstract : Specific properties for potential sensor materials for dark matter detection are defined. A materials informatics approach is discussed on the example of the organic materials database OMDB. Three potential candidate materials are identified. Two materials are tiny gap semiconductors. The third is a Dirac‐line semimetal which gaps out under the tiny spin‐orbit coupling present in the material.